Comparative Analysis of Surgical Approaches in the Treatment of Proximal Humerus Fractures: A Retrospective Study - J Sivaram; Shubham Asati; Himanshu Bothra; Gaurav S. Pagare; Supantha Panja; Reshma Tirunamalli; Jasmine Kalsi (Wolters Kluwer Medknow Publications, 2024)
Background: "Proximal humerus fractures [PHFs]" are common orthopedic injuries, often requiring surgical intervention for optimal outcomes. However, the choice of surgical approach remains controversial, with varying outcomes reported in the literature. Methods: A retrospective research was overseen among subjects who had surgery for PHFs. Three surgical approaches were compared: "Open Reduction Internal Fixation (ORIF)", "Hemiarthroplasty [HA]", and "Reverse Shoulder Arthroplasty [RSA]". Demographic data, fracture characteristics, surgical details, and postoperative outcomes were analyzed. Results: ORIF confirmed smaller operative time and shorter complication levels compared to HA and RSA. Complications included surgical site infection, implant-related issues, and reoperation. Age, fracture type, and surgeon experience influenced the choice of surgical approach. Conclusion: This research provides valuable insights into the outcomes of different surgical approaches for PHFs. ORIF may offer advantages in select cases, but individualized treatment decisions are necessary. Further research is warranted to refine treatment algorithms and optimize patient outcomes.